The Influence of Conformity on Consumption Behavior of Indonesian NCTzens in The Islamic Economics Perspective - Ardiyani, Audwina Hati; Pramono, Adi Tri; Muh Shadiqul Fajri AF (The Es Economics and Entrepreneurship, 2023)
This study aims to determine the influence of conformity on the consumption behavior of NCTZEN Indonesia in an Islamic economic perspective. The method used in this study is a quantitative research method. The population in this study was a fandom from NCTZEN Indonesia with a sample of 55 respondents. In this study, the sampling technique used was snowball sampling. The analytical tools used are the reliability test reliability test Simple linear regression normality test correlation coefficient of determination coefficient and hypothesis test (t test) treated using IBM SPSS 26 0 version. The result showed that Conformity has no significant effect on the Consumption Behavior of NCTzen Indonesia from an Islamic Economic perspective. NCTzen Indonesia's behavior in carrying out consumption activities is not in accordance with the provisions of Islamic economics. However, the implementation of consumption behavior by NCTzen Indonesia is increasingly starting to understand Islamic economic consumption.